SELF-EFFICACY DAN SELF-CARE MANAGEMENT PADA PENDERITA HIPERTENSI - Andreas Rantepadang; Bella Elisabeth Sabathama Hadibrata (Klabat Journal of Nursing, 2023)
With the increasing number of hypertensive patients who often appear without symptoms and are influenced by various factors, a technique for controlling blood pressure is needed such as self-care management and self-efficacy. The purpose of this study was to determine the relationship between self-efficacy and self-care management in patients with hypertension. Method: This research is a quantitative type with a cross-sectional approach. Samples were taken using a total sampling technique with a total of 66 samples. The instruments used are the Self-efficacy to Manage Hypertension-Five Item Scale and Hypertension Self-Care Management Behavior. Results: The results showed that 53 (80.3%) respondents had poor self-efficacy, and 54 (81.8%) patients had good self-care management. There was a significant relationship between self-efficacy and self-care management in hypertension sufferers with a p-value value of 0.000. It is recommended that people with hypertension can increase their self-efficacy in order to achieve good and stable self-care management of hypertension, for future researchers to be able to use a self-efficacy questionnaire that more accurately determines the range of good and bad, and also adds other variables that can be factors that influence affect self-care management such as education level, history of knowledge, gender, and lifestyle. Keywords: Hypertension, Self-Care Management, Self-Efficacy Abstrak Peningkatan jumlah penderita hipertensi disetiap kalangan usia, sering muncul tanpa adanya gejala dan dipengaruhi oleh berbagai faktor, diperlukan suatu teknik dalam mengontrol tekanan darah seperti self-care management dan self-efficacy. Tujuan penelitian adalah mengetahui hubungan self-efficacy dengan self-care management pada penderita hipertensi. Metode: Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional. Sampel yang diambil menggunakan teknik total sampling dengan jumlah 66 sampel. Instrumen yang digunakan adalah Self-efficacy to Manage Hypertension-Five Item Scale dan Perilaku Manajemen Perawatan Diri Hipertensi. Hasil penelitian menunjukan 53 (80.3%) responden memiliki self-efficacy buruk, dan 54 (81.8%) penderita memiliki self-care management yang baik, ada hubungan yang signifikan antara self-efficacy dengan self-care management pada penderita hipertensi dengan nilai p-value 0,000. Direkomendasikan untuk penderita hipertensi dapat meningkatkan self-efficacy agar tercapainya self-care management hipertensi yang baik dan stabil, untuk peneliti selanjutnya agar dapat menggunakan kuesioner self-efficacy yang lebih akurat menentukan rentang baik dan buruk, dan juga menambahkan variabel lain yang dapat menjadi faktor yang mempengaruhi self-care management seperti tingkat pendidikan, riwayat pengetahuan, jenis kelamin dan pola hidup. Kata kunci: Hipertensi, Self-Care Management, Self-efficacy